A comprehensive overview of the effects of urbanisation on sexual selection and sexual traits. (9th March 2022) - Cronin, Andrew D.; Smit, Judith A. H.; Muñoz, Matías I.; Poirier, Armand; Moran, Peter A.; Jerem, Paul; Halfwerk, Wouter
ABSTRACT: Urbanisation can affect mating opportunities and thereby alter inter‐ and intra‐sexual selection pressures on sexual traits. Biotic and abiotic urban conditions can influence an individual's success in pre‐ and post‐copulatory mating, for example through impacts on mate attraction and mate preference, fertilisation success, resource competition or rival interactions. Divergent sexual selection pressures can lead to differences in behavioural, physiological, morphological or life‐history traits between urban and non‐urban populations, ultimately driving adaptation and speciation. Most studies on urban sexual selection and mating interactions report differences between urban and non‐urban populations or correlations between sexual traits and factors associated with increased urbanisation, such as pollution, food availability and risk of predation and parasitism. Here we review the literature on sexual selection and sexual traits in relation to urbanisation or urban‐associated conditions. We provide an extensive list of abiotic and biotic factors that can influence processes involved in mating interactions, such as signal production and transmission, mate choice and mating opportunities. We discuss all relevant data through the lens of two, non‐mutually exclusive theories on sexual selection, namely indicator and sensory models. Where possible, we indicate whether these models provide the same or different predictions regarding urban‐adapted sexual signals and describe different experimental designs that can be useful for the different models as well as to investigate the drivers of sexual selection. We argue that we lack a good understanding of: ( i ) the factors driving urban sexual selection; ( ii ) whether reported changes in traits result in adaptive benefits; and ( iii ) whether these changes reflect a short‐term ecological, or long‐term evolutionary response. We highlight that urbanisation provides a unique opportunity to study the process and outcomes of sexual selection, but that this requires a highly integrative approach combining experimental and observational work.